VOCABULARY KNOWLEDGE IN RELATION WITH STUDENT’S READING COMPREHENSION: A REVIEW - Alpino Susanto (INOVISH JOURNAL, 2018)
In language learning, vocabulary knowledge is considered as a dominant factor, either as a second or a foreign language. Vocabulary knowledge is justified as a crucial site to overall language acquisition process. There are a lot of unknown words that language learners encounter while they are reading are probably the very basic and fundamental reasons. In this notion, the learner may have difficulties in comprehending the text they are reading. Language learner and educators alike know that many of the reading comprehension breakdowns that experienced by students involve word recognition and lexical access course. Hence, this paper is an attempt to extend knowledge of vocabulary and its relationship with reading comprehension. Through the review of various views in vocabulary role and reading comprehension, intended to broaden knowledge of vocabulary and its relationship with reading comprehension.Â